1992
DOI: 10.1016/s0735-1097(10)80282-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental modulation of myocardial mechanics: Age- and growth-related alterations in afterload and contractility

Abstract: Somatic growth is associated with alterations in myocardial mechanics in children with heart disease and in most animal models of congenital heart disease. However, the effect of age and body size on myocardial contractility and loading conditions in normal infants and children is not known. Therefore, 256 normal children aged 7 days to 19 years (34% less than 3 years old) were evaluated with noninvasive indexes of left ventricular contractility and loading conditions. Two-dimensional and M-mode echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 263 publications
(140 citation statements)
references
References 68 publications
6
134
0
Order By: Relevance
“…In the present study, we have shown that the measures of left heart size, including LVDD, LVSD, and aortic annulus dimension, correlate with worsening anemia. The LV mass showed a significant increase in all SCA patients, relative to published normal values [24], and its severity progressed with the degree of anemia. Cardiac output also increased in proportion to the degree of anemia.…”
Section: Clinical Findingsmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present study, we have shown that the measures of left heart size, including LVDD, LVSD, and aortic annulus dimension, correlate with worsening anemia. The LV mass showed a significant increase in all SCA patients, relative to published normal values [24], and its severity progressed with the degree of anemia. Cardiac output also increased in proportion to the degree of anemia.…”
Section: Clinical Findingsmentioning
confidence: 60%
“…Cardiac dimensions for the SCA patients were compared to values from the normal predicted equations [24], and each observed value was then expressed as a standard deviation (SD) from the normal predicted value (Zscore).…”
Section: Discussionmentioning
confidence: 99%
“…13 Left ventricular end-diastolic dimension, free wall thickness, septal thickness, and mass were expressed as z scores relative to the distribution of these measurements versus body surface area in normal children, 14 and fractional shortening was expressed as the z score relative to age. 15 Incidence estimates are based on the prospective cohort from the 2 geographic regions for 1996 through 2000 using methods described elsewhere. 12 The distributions of categorical variables by groups were compared using the Fisher exact test unless otherwise noted.…”
Section: Colan Et Al Hypertrophic Cardiomyopathy In Childrenstatisticmentioning
confidence: 99%
“…29 Afterload (>74 g/cm 2 5 abnormal) was approximated by left ventricular end-systolic wall stress. 30 …”
Section: Study Assessments Cardiac Assessmentmentioning
confidence: 99%